2022
DOI: 10.1371/journal.pone.0268644
|View full text |Cite
|
Sign up to set email alerts
|

Calcium imaging in intact mouse acinar cells in acute pancreas tissue slices

Abstract: The physiology and pathophysiology of the exocrine pancreas are in close connection to changes in intra-cellular Ca2+ concentration. Most of our knowledge is based on in vitro experiments on acinar cells or acini enzymatically isolated from their surroundings, which can alter their structure, physiology, and limit our understanding. Due to these limitations, the acute pancreas tissue slice technique was introduced almost two decades ago as a complementary approach to assess the morphology and physiology of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…These characteristics have been thoroughly defined in tissue derived from both rodents and humans (Murphy et al., 2008; Williams et al., 1978). However, exclusively the experiments were performed in dissociated single cells, isolated acini or more recently in organotypic lobule preparations (Gryshchenko et al., 2021; Liang et al., 2017; Marolt et al., 2022; Won et al., 2011) . The impact of these noted caveats associated with ex vivo studies and the spatiotemporal properties of Ca 2+ signals were not known.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics have been thoroughly defined in tissue derived from both rodents and humans (Murphy et al., 2008; Williams et al., 1978). However, exclusively the experiments were performed in dissociated single cells, isolated acini or more recently in organotypic lobule preparations (Gryshchenko et al., 2021; Liang et al., 2017; Marolt et al., 2022; Won et al., 2011) . The impact of these noted caveats associated with ex vivo studies and the spatiotemporal properties of Ca 2+ signals were not known.…”
Section: Discussionmentioning
confidence: 99%
“…Multicellular recordings of membrane potential or intracellular calcium concentration are typically used as input signals. Network principles have thus been used to elucidate the connectivity patterns in neurons ( 40 44 ), astrocytes ( 45 ), pituitary endocrine cells ( 46 , 47 ), lens epithelium cells ( 48 , 49 ), hepatocytes ( 50 ), mammary epithelium cells ( 51 ), endothelial cells ( 52 ), and pancreatic acinar cells ( 53 ). Network analyses were introduced to the islet community a decade ago and are increasingly seen as a valuable tool to examine and quantify collective activity patterns in the pancreatic islets of Langerhans ( 18 , 54 69 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, we have established a new preclinical methodological pipeline for studying changes in acinar cell structure during the development of diet-induced obesity and T2DM and found that early during the development of obesity and progression from compensated to decompensated diabetes ( Paschen et al, 2019 ), acinar cells already show striking ultrastructural signs of functional adaptation to increased workload and dysfunction affecting intracellular organelles in a rather non-selective manner and before changes in tissue or plasma levels and activity of amylase become apparent. Our approach is methodologically compatible with functional studies of acinar cells ( Marolt et al, 2022 ), with morphological and functional studies of other cell types in the exocrine and endocrine parts of the pancreas ( Marciniak et al, 2014 ; Stožer et al, 2021 ), as well as with more quantitative image-analysis approaches ( Klemen et al, 2022 ). These should be combined in the future to obtain more answers regarding the relationship between structural and functional changes in endocrine, ductal, and acinar cells during disease progression, regarding the relationship between the various cell types, as well as regarding the reversibility of these changes.…”
Section: Discussionmentioning
confidence: 98%